Analysis Of Mathematical Logical Thinking Skills In Solving Arithmetic Problems: A Study Of Introverted - Popy Fahira; Putri Yulia (Universitas Wiralodra, 2025)
This study examines students’ logical-mathematical thinking skills in solving arithmetic problems by considering introverted and extroverted personality types. A descriptive qualitative approach with a case study design was employed, involving four ninth-grade students selected through purposive sampling. Data were collected using a logical thinking ability test, the MBTI personality questionnaire, and structured interviews. The results showed that overall, students’ logical-mathematical thinking skills were relatively low, with most participants categorized as “Very Low.” Extroverted students demonstrated greater variation in performance, with one student achieving slightly higher logical thinking skills than the others. However, no significant differences were observed between introverted and extroverted students in their logical reasoning and problem-solving abilities. These findings suggest that personality type alone does not substantially determine students’ logical-mathematical thinking skills; other factors, such as learning motivation, conceptual understanding, and instructional strategies, also contribute to these outcomes. This study highlights the importance of implementing tailored instructional approaches to enhance students’ focus, motivation, and constructive feedback in supporting the development of logical thinking skills among students with diverse personality types.